Synthesis, Spectroscopic and Thermodynamic Studies of Metal Complexes with Schiff Bases Derived from 2-[5-(Pyridin-2-Ylmethylene)-amino] 1,3,4-Oxadiazol-2-yl-Phenol - Shaalan, Naser; Hassan, Sahar S; Al-Hamdani, Abbas Ali Salih (Al-Nahrain Journal of Science, 2018)
New metal complexes of the ligand 2-[5-(Pyridin-2-ylmethylene)-amino] 1,3,4-thiadiazol-2-yl-phenol (L) with the metal ions Co(II), Ni(II), Cu(II) and Zn(II) were prepared in alcoholic medium. The Schiff base was condensed [2-pyridine carbxaldehyde] with [2-amino-5-(phenyl-1,3,4-oxadiazole] in alcoholic medium. Two tetradentate Schiff bases ligand were used for complexation upon two metal ions of Co2+, Ni2+, Cu2+ and Zn2+ as dineucler formula M2L2. The synthesized compound and their metal complexes were characterized by FTIR Spectroscopy, electronic spectroscopy, Elemental analysis, magnetic susceptidbility measurements, thermal analysis , 1H-NMR spectra, and mass spectra. The activation thermodynamic parameters such as ΔE*, ΔH*, ΔS* and ΔG* were calculated from the TGA curve using Coats-Red fern method. From the measurements, structures of the complexes were proposed.